2021
DOI: 10.3390/risks9090163
|View full text |Cite
|
Sign up to set email alerts
|

Economic Policy Uncertainty and Cryptocurrency Market as a Risk Management Avenue: A Systematic Review

Abstract: Cryptocurrency literature is increasing rapidly nowadays. Particularly, the role of the cryptocurrency market as a risk management avenue has got the attention of researchers. However, it is an immature asset class and requires gaps in current literature for future research directions. This research provides a systematic review of the vast range empirical literature based on the cryptocurrency market as a risk management avenue against economic policy uncertainty (EPU). The review discovers that cryptocurrenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…Next step, shows the evaluation between all the pair-wise manner columns based on the Euclidean distance process which gives us the augmentation matrix distance  as following Equation 2: 2 (2)…”
Section: Methodsmentioning
confidence: 99%
“…Next step, shows the evaluation between all the pair-wise manner columns based on the Euclidean distance process which gives us the augmentation matrix distance  as following Equation 2: 2 (2)…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the need for customer data mining and analysis tools as a prerequisite for adopting appropriate marketing and CRM approaches to satisfy and retain customers is felt more than ever. One of such data mining techniques is customer segmentation, which involves dividing heterogeneous customers into homogeneous groups with similar purchasing behaviors and patterns in order to make it easier to understand how they behave and develop the appropriate marketing and CRM strategy accordingly [8].…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al (2021) demonstrated that cryptocurrencies act as a hedge for higher EPU but not in moderate or low EPU. Furthermore, Haq et al (2021) conducted a systematic review of empirical literature based on the cryptocurrency market and discovered the mixed connectedness pattern of cryptocurrency with all national EPU. This heterogenous correlation patterns suggest future research avenues in the cryptocurrency market.…”
Section: Introductionmentioning
confidence: 99%